Introduction - Northup, Nancy (Columbia Journal of Gender and Law, 2009)
This volume is the outgrowth of a panel discussion on New Scholarship on Reproductive Rights held at Columbia Law School on October 20, 2008 to celebrate the establishment of a new joint fellowship program of the Center for Reproductive Rights2 and Columbia Law School-The CRR-CLS Fellowship-as well as an initiative by the Center to stimulate scholarship and teaching on reproductive health and human rights. In the last decade, there have been groundbreaking cases from national courts as well as regional and international human rights bodies. These cases are not widely taught in U.S. law schools nor widely incorporated into legal scholarship. The emerging norms stemming from these cases, grounded in rights to equality, dignity, health, autonomy, freedom from cruel and degrading treatment, and non-discrimination, arguably provide more robust protection for women’s health and reproductive self-determination than constitutional rights in the United States. Whereas the U.S. Supreme Court has ruled in the past that pregnancy discrimination does not violate equal protection guarantees, foreign courts and international tribunals have recognized that discrimination against pregnant women is sex discrimination, and that it is a violation of guarantees of non-discrimination to restrict access to health services necessary to women. The underlying premise of the fellowship is that there are paradigm-shifting developments in transnational law on reproductive health and human rights that could invigorate scholarship in the U.S. legal community.